Facials - Milady; Delmar Learning ([Clifton Park, NY?] : Thomson Delmar Learning, 2007)
"A valuable resource for esthetics professionals ... will show you how to apply the principles of physiology to analysis, expertly determining skin types and applying customized skin care treatments to address your client's individual needs. Industry experts provide guidance on everything from sanitation protocols and massage techniques to specialized mask application for various skin types and conditions. You will also learn how your personal presentation, room set-up, and ambience contribute to creating an optimal experience for your clients"--Container.
Facial prep -- Skin analysis -- Basic facial -- Specialized skin treatments.
"Part of a three-DVD series"--Container.
Digital video disc.
English; Optional subtitles in English.
Keywords: Face -- Care and hygiene; Beauty culture